Contemporary interventional management of pulmonary embolism. Issue 5 (May 2023) - Gupta, A.; Thulasidasan, N.; Mak, S.M.; Rawal, B.; Padley, S.P.G.; Karunanithy, N.
Abstract : Minimally invasive interventional techniques are being utilised more frequently in the management of acute and chronic pulmonary emboli; however, robust clinical evidence is only emerging for the utilisation of these techniques. Hence, there is a need for a robust mechanism of patient selection and careful consideration of the benefits and risks of the interventions. In this review, we discuss the risk stratification mechanisms; the role of the multidisciplinary pulmonary embolism response team to support decision-making; and describe the various commonly used interventional techniques and how these can be integrated into treatment strategies for the benefit of our patients.